The safety and effectiveness of percutaneous nephrolithotomy in solitary kidney aging male patients: our single-center experience. (4th December 2020) - Besiroglu, Huseyin; Merder, Erkan; Dedekarginoglu, Galip
Abstract: Objective: To assess the safety and effectiveness of percutaneous nephrolithotomy (PCNL) in aging male patients with a solitary kidney. Methods: Among the patients undergoing PCNL between December 2009 and September 2014, 16 patients with solitary kidney (group 1) over the age of 40 were included in the analysis. Twenty patients with bilateral kidney patients (group 2) were included in the analysis, which constituted an age-matched control group. The patients' characteristics, stone characteristics, intraoperative and postoperative outcomes, including bleeding and transfusion rates, operative time, complications, hospital stay, stone-free rates (SFR) and renal function were evaluated. Results: Mean age of the patients in groups 1 and 2 were 63.7 (range 48–73) and 64.8 (range 48–77). Mean stone size was 814 ± 390 mm 2 in group 1, and 820 ± 405 mm 2 in group 2 with no statistical significance ( p = .35). The final SFR in the solitary kidney and bilateral kidney group was 87.5 and 90% ( p = .07). Bleeding requiring transfusion, prolonged leakage from nephrostomy tract, mean operation time and access number were comparable between two groups ( p > .05). However, the nephrostomy removal and hospital stay time were longer in the solitary kidney group ( p < .05). The rate of perioperative DJ insertion was also higher in solitary kidney patients. A significant improvement was detected in creatinine and glomerular filtration rate levels in the sixth months after surgery in solitary kidney patients ( p < .05). Conclusion: These results indicate that PCNL is a safe and effective method in aging male patients with a solitary kidney.